Glucocorticoid and thyroid hormones transcriptionally regulate growth hormone gene expression. - Evans, R M (1982)
In order to define the molecular mechanisms by which glucocorticoids and thyroid hormone act to regulate growth hormone gene expression, the sites at which they exert their effects on growth hormone biosynthesis were examined in vivo and in a pituitary cell line. Glucocorticoids were shown to rapidly increase accumulation of growth hormone mRNA and nuclear RNA precursors. Glucocorticoids and thyroid hormone were shown to rapidly and independently increase growth hormone gene transcription. These events are shown to occur physiologically in animals and further establish the importance of growth hormone gene expression as a model for steroid regulation.